2013
DOI: 10.4068/cmj.2013.49.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cariogenic Bacteria in Saliva of Cancer Patients

Abstract: This study examined salivary flow and salivary pH and the prevalence and levels of cariogenic bacteria in the saliva of oncological patients and healthy controls. Quantitative real-time polymerase chain reaction was used to assess the levels of microbes including Streptococcus mutans, Streptococcus sobrinus, Lactobacillus salivarius, and Lactobacillus acidophilus in the saliva of 41 patients with a solid tumor (SO), 30 patients with a hematologic malignancy (HE), and 40 healthy controls. Salivary flow and pH w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
6
0
1
Order By: Relevance
“…[ 19 ] Kang et al . [ 20 ] found that salivary pH was significantly lower in cancer patients. Lime which is a major component of betel quid preparation causes changes in oral environment of chewers.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Kang et al . [ 20 ] found that salivary pH was significantly lower in cancer patients. Lime which is a major component of betel quid preparation causes changes in oral environment of chewers.…”
Section: Discussionmentioning
confidence: 99%
“…This methodology is recommended for verifying cases of hyposalivation because it is subject to a lower influence of external factors [ 14 , 18 , 19 ]. Due to operational questions, and seeking to minimize the influence of the circadian rhythm of salivation, collections were always made in the morning period, 1 hour after the last time of tooth brushing and eating, under the same conditions of positioning, lighting, and sounds [ 18 , 19 ]. Initially, the patients were asked to remain seated, in a 90° position, without speaking and moving, with the upper limbs resting on the lower limbs.…”
Section: Methodsmentioning
confidence: 99%
“…This change in the mucosa can progress to cell desquamation resulting in symptomatic ulcer, hindering the speech power and alimentation [20]. For most researchers, is mucositis caused by chemotherapy and occurs due to a dynamic process resulting in the destruction of basal cells and its prevalence is among 40% and 76% of 29 patients undergoing chemotherapy [21].…”
Section: Discussionmentioning
confidence: 99%
“…Conducting a thorough search, we could find only 2 researches; one evaluated [21] children aged between 5 and 12 years and obtained pH 7.8 and rest of the other children 5-11 years and obtained rest of pH 7:27.…”
Section: Discussionmentioning
confidence: 99%